Unlocking Economic Value in Healthcare: Applying Importance-Performance Mapping Analysis (IPMA) to Identify Key Drivers of Patient Satisfaction in Medical Check-Up Services - Sidik, Nuraini; Antonio, Ferdi (International Journal of Economics Development Research (IJEDR), 2024)
Medical check-up services are essential for clinics to enhance patient satisfaction and loyalty. This study examines the effectiveness of the service quality model, encompassing infrastructural quality, interactional quality, outcome quality, procedural quality, and personnel quality, in measuring satisfaction with medical check-up services. A quantitative survey was conducted with patients, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Importance-Performance Map Analysis (IPMA) was applied to identify key indicators for improvement and areas of strength. This study obtained 211 respondents who had undergone medical check-ups, and questionnaires were distributed directly at the clinicThe results showed that outcome quality has the strongest influence on satisfaction (0.362), followed by procedural quality (0.242), while personnel quality had the weakest effect (0.121). The IPMA highlighted indicators of Outcome Quality 1 (comprehensive medical reports) and Procedural Quality 1 (efficient workflows) as priority areas for improvement, while Outcome Quality 2 (clear and understandable results) demonstrated high performance and importance, warranting continued focus. These findings suggest that improving clinical outcomes and streamlining procedural efficiency are crucial for enhancing satisfaction. The study provides practical recommendations for clinic managers to prioritize service improvements that align with patient expectations, thereby enhancing overall satisfaction and loyalty.